Chest physiotherapy in cystic fibrosis - Adjuncts and alternatives - B. Oberwaldner; M. S. Zach (AOSIS, 1986)
Chest physiotherapy is part of the long-term respiratory management of cystic fibrosis. Since compliance is often poor, effective and practical alternatives need to be sought. A preliminary study investigated the effect of weeks swimming training on the respiratory status of 10 patients while continuing their chest physiotherapy programme. Pulmonary function improved significantly after the course viz. FEV1: 82% predicted ± 24 to 90% predicted ± 23, p 0,05. Ten weeks after the trial most of the measurements had returned to their pre swimming levels. It was noted that sputum production on swimming days was higher than on non-swimming days. In a second study 12 children with cystic fibrosis participated in a training programme which included a variety of sports. Physiotherapy was discontinued during this period. Again pulmonary function improved significantly after the course viz. FEV1: 71% predicted ±23 to 79% predicted ± 23, p 0,01. Most values had returned to pre-training levels 8 weeks after the programme had ended. A current study is investigating the possible therapeutic benefit of a one-way breathing valve with increased expiratory resistive loads. Preliminary results indicate increased mobilisation of obstructing secretions as well as a significant improvement of pulmonary function. One can conclude that some highly effective and practical adjuncts and alternatives to the daily physiotherapy routine for cystic fibrosis do exist